Philosophy And Technologi In The Digital Era - Humau, Yulinda Makdalena; Asadama, Mia; Lelo, Kaleb; Liufeto, Desi Alyani; Lasena, Yeni Felpina (TRANSFORMASI : JURNAL PENGABDIAN PADA MASYARAKAT, 2025)
The advancement of digital technology has brought fundamental changes to various aspects of human life, ranging from ways of communication to how knowledge is produced and disseminated. A lecturer in the Philosophy of Science course addressed the technological revolution in the digital era. Students in the Early Childhood Christian Education program at IAKN Kupang utilized technology wisely through a seminar activity with the theme "Philosophy and Technology in the Digital Era."The advancement of digital technology has brought fundamental changes to various aspects of human life, ranging from ways of communication to how knowledge is produced and disseminated. A lecturer in the Philosophy of Science course addressed the technological revolution in the digital era. Students in the Early Childhood Christian Education program at IAKN Kupang utilized technology wisely through a seminar activity with the theme "Philosophy and Technology in the Digital Era."The implementation of the activity involved several stages: planning, execution, and evaluation. The final results of this activity showed both positive and negative impacts experienced by students in using technology, as well as how to reconcile thoughts with actions in the real world